2010
DOI: 10.1093/humrep/deq298
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of endometrial olfactomedin expression and its suppressive effect on spheroid attachment onto endometrial epithelial cells

Abstract: Decreased expression of Olfm during the receptive phase of the endometrium may allow successful trophoblast attachment for implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…To demonstrate how the E 2 and P levels affect spheroid attachment, an initial step of implantation, we established a spheroidendometrial cell coculture model (13,14). Our study showed that excessively high E 2 and P levels suppressed trophoblastic spheroid attachment onto endometrial epithelial cell lines, resembling the clinical situation as demonstrated in earlier studies (8,29,30).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…To demonstrate how the E 2 and P levels affect spheroid attachment, an initial step of implantation, we established a spheroidendometrial cell coculture model (13,14). Our study showed that excessively high E 2 and P levels suppressed trophoblastic spheroid attachment onto endometrial epithelial cell lines, resembling the clinical situation as demonstrated in earlier studies (8,29,30).…”
Section: Discussionsupporting
confidence: 70%
“…Adhesion of Jeg-3 spheroids to endometrial Ishikawa cells was quantified by using an adhesion assay as described elsewhere (11,13). In the coculture study, the medium of Jeg-3 and Ishikawa cells were changed to phenol red-free DMEM/F12 supplemented with 10% charcoal-stripped fetal bovine serum.…”
Section: Cell Culture and Spheroid-endometrial Cell Attachment Assaymentioning
confidence: 99%
“…A high P level is associated with a lower Olfm1 expression level during the implantation window in human endometrium, and suppression of Olfm1 expression enhances spheroid attachment in OE-E6/E7 cells (36). Therefore, steroid hormones likely modulate the effect of embryo-derived hCG in activating the hCG/LH receptor, through the ERK/Wntsignaling pathway, to suppress Olfm1 expression in human fallopian tubes.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, Olfm1 regulated the Wnt-signaling pathway and modulated retinal axon elongation (35). Previously, we used a trophoblastic spheroid (JAr)-endometrial epithelial cell (Ishikawa) co-culture model to demonstrate the suppressive effect of Olfm1 on JAr spheroid attachment on Ishikawa cells (36). However, the way in which Olfm1 is regulated at the feto-maternal interface remains largely unknown.…”
mentioning
confidence: 99%
“…Nonspecific binding was blocked with 5% bovine serum albumin diluted in phosphate-buffered saline. The sections were then successively incubated with antibodies against APN (Abcam), integrin-b1 (Millipore), Mucin4 (Abcam), or vitroectin (Abcam), and respective horseradish peroxidase conjugated secondary antibodies (DAKO) using the procedures described previously elsewhere (17). Biotinylated cells were detected by the Vectastain ABC reagent (Vector Laboratories) and 3,3 0 -diaminobenzidine solution (DAKO).…”
Section: Immunohistochemical Staining and Immunostaining Of The Biotimentioning
confidence: 99%